Bacterial Meningitis in Adults - Michael Fitch (Association of American Medical Colleges, 2011)
Abstract Bacterial meningitis is a life threatening infection of the central nervous system with significant morbidity and mortality. Clinicians are challenged with using patient history, physical examination findings, and laboratory studies to make diagnoses and begin timely treatment when indicated. This resource is a video lecture presentation intended for educational use by practicing medical professionals and those preparing to become medical practitioners. The information presented here for the diagnosis and treatment of bacterial meningitis in adults has been used with learners from multiple clinical specialties and levels of training. This lecture was initially developed in 2003 as a live lecture activity, and has been continuously revised and presented by the author over 15 times at local, regional, national, and international educational meetings since that time. Learners have included medical students, physician assistant students, resident physicians, emergency medicine faculty, and practicing clinicians from multiple specialties throughout the world. Formal written evaluations and informal verbal feedback was collected throughout the past 8 years of the development process and used to improve the presentation and content. The clinical content here has served as the basis for several peer reviewed published manuscripts by the author, and the material has been very well received by practicing community physicians of various clinical specialties, academic faculty and resident physicians, midlevel providers, and medical students. Having presented this material to a wide variety of learners at all stages of medical education over many years, significant revisions have been made based on learner type and anticipated audience needs. The final video version of this resource strikes a balance between the information felt to be important for each of these groups of learners while retaining a concise format. Numerous references are provided for clinicians wanting additional information about any of the topics discussed in this resource.